Non‐equivalence in old‐ and new‐flagellum daughter cells of a proliferative division in Trypanosoma brucei - Abeywickrema, M; Vachova, H; Farr, H; Mohr, T; Wheeler, RJ; Lai, D-H; Vaughan, S; Gull, K; Sunter, JD; Varga, V (Wiley, 2019)
Differentiation of Trypanosoma brucei, a flagellated protozoan parasite, between life cycle stages typically occurs through an asymmetric cell division process, producing two morphologically distinct daughter cells. Conversely, proliferative cell divisions produce two daughter cells, which look similar but are not identical. To examine in detail differences between the daughter cells of a proliferative division of procyclic T. brucei we used the recently identified constituents of the flagella connector. These segregate asymmetrically during cytokinesis allowing the new‐flagellum and the old‐flagellum daughters to be distinguished. We discovered that there are distinct morphological differences between the two daughters, with the new‐flagellum daughter in particular re‐modelling rapidly and extensively in early G1. This re‐modelling process involves an increase in cell body, flagellum and flagellum attachment zone length and is accompanied by architectural changes to the anterior cell end. The old‐flagellum daughter undergoes a different G1 re‐modelling, however, despite this there was no difference in G1 duration of their respective cell cycles. This work demonstrates that the two daughters of a proliferative division of T. brucei are non‐equivalent and enables more refined morphological analysis of mutant phenotypes. We suggest all proliferative divisions in T. brucei and related organisms will involve non‐equivalence.